Evaluating National Health Systems: The Case of the General Health System of Cyprus Through a Survey - Evripides, George; Christodoulides, Paul (My University, 2026)
A medical health system (MHS) comprises organizations, professionals, and resources working together to maintain and improve health at both individual and societal levels. Evaluating MHS performance is essential to ensure quality, equity, and sustainability. This study attempts an initial assessment of Cypriots' views on the newly developed General Health System (GHS) of Cyprus, a national MHS.
Keywords: satisfaction with MHS; descriptive statistics; healthcare; medical health system; questionnaire